(untitled) (PerCursos, 2025)
This article focuses on indigenous higher education in Brazil. The objective is to present some proposals for enabling the indigenous population to remain in universities. The article has a qualitative approach, based on a literature review and a case study carried out with students enrolled at the State University of Bahia between 2015 and 2020. The case study is part of the doctoral research developed at the Federal University of Bahia - UFBA, called “Indigenous peoples at a multi-campus university: academic experiences and reterritorialization processes”. The analyzes lead to the conclusion that although access of indigenous peoples to higher education is a reality in Brazil, there are difficulties in ensuring the adequate retention of Indigenous students. Therefore, the proposals presented in the article are timely and, if implemented, could improve higher education in general.